Impact of Debt Sustanability on Nigerian Economic Development - Uchechi, Ukangwa Jane; Iheukwumere, Ikechi Victor; Ogbonna, Ben M. (Central Asian Journal of Innovations on Tourism Management and Finance, 2022)
This study is carried out to determine the impact of external debt sustainability on Nigerian economic development from 1980-2015. This study is embarked upon due to the slow pace of economic growth occasioned by low human development index, low level of GDP, balance of payment deficit, low level of investment and infrastructure despite the excess external borrowings by the government. The data for this study is secondarily sourced from the CBN statistical bulletin of various issues and world development index. Five research questions and research hypotheses were formulated to guide the study. The data were subject to stationery test using Augmented Dickey Fuller unit root test statistic. The data were found to be stationery at their first difference. The data were also found to be co-integrated in using Johansen co-integration technique. The findings of the study after using the parsimonious Vector Error correction technique revealed that external debt sustainability is positively related to GDP, net export and human development index. Also debt sustainability did not have any impact on investment and infrastructure. It is recommended that government should make judicious use of borrowed funds and ensure that borrowed funds are strictly invested in capital projects.